An extended framework of cages formed of pre-synthesised and functionalised heterometallic cages1. Issue 17 (28th February 2015) - Whitehead, George F. S.; Teat, Simon J.; Gagnon, Kevin J.; Timco, Grigore A.; Winpenny, Richard E. P.
<x xml:space="preserve">Abstract</x> A metal–organic framework is reported which is formed from reacting a heterometallic ring, which is functionalised to act as a 4, 4′-bipyridyl linear linker, and an oxo-centred metal-triangle.